Energetic Metal–Organic Frameworks Derived Highly Nitrogen‐Doped Porous Carbon for Superior Potassium Storage. Issue 43 (4th October 2020) - Tong, Huigang; Wang, Changlai; Lu, Jian; Chen, Shi; Yang, Kang; Huang, Minxue; Yuan, Qing; Chen, Qianwang
Abstract: The carbonaceous materials with low cost and high safety have been considered as promising anodes for potassium‐ion batteries (PIBs). However, it is still a challenge to design a carbonaceous material with long cycle life and high rate performance due to the poor K + reaction kinetics. Herein, this article reports a N‐doped porous carbon framework (NPCF) with a high nitrogen content of 13.57 at% within high doping level of the pyrrolic N and pyridinic N, which exhibits a high reversible capacity of 327 mA h g −1 over 100 cycles at a current density of 100 mA g −1, excellent rate capability (144 and 105 mA h g −1 at 10 and 20 A g −1, respectively) and great cyclability of 258.9 mA h g −1 after 2000 cycles at 1 A g −1 . Such a high rate performance and excellent cycling stability anode material is seldom reported in PIBs. Density functional theory (DFT) calculations reveal that the pyrrolic and pyridinic N‐doping are helpful to enhance the K adsorption ability, thereby increasing the specific capacity. Abstract : A novel highly nitrogen‐doped porous carbon framework derived from the energetic metal–organic framework is applied as anode for potassium ion batteries, delivering excellent rate performance, and great cyclability. Density functional theory calculations reveal that the pyrrolic and pyridinic N‐doping are helpful to enhance the K adsorption ability, thereby increase the specific capacity.